2015
DOI: 10.1124/dmd.115.063271
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of OTS167 in Humans Is Catalyzed by UDP-Glucuronosyltransferases UGT1A1, UGT1A3, UGT1A8, and UGT1A10

Abstract: OTS167 is a potent maternal embryonic leucine zipper kinase inhibitor undergoing clinical testing as antineoplastic agent. We aimed to identify the UDP-glucuronosyltransferases (UGTs) involved in OTS167 metabolism, study the relationship between UGT genetic polymorphisms and hepatic OTS167 glucuronidation, and investigate the inhibitory potential of OTS167 on UGTs. Formation of a single OTS167-glucuronide (OTS167-G) was observed in pooled human liver (HLM) (K m = 3.4 6 0.2 mM), intestinal microsomes (HIM) (K m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
(64 reference statements)
0
6
0
Order By: Relevance
“… 18 , 19 For example, effect of rs6706232 on OTS167 (a novel synthetic anticancer agent molecule undergoing clinical development) glucuronidation formation rates was merely modest suggesting this SNP may not significantly contribute to OTS167 clearance. 20 In our study, rs6706232 was first found related with risperidone treatment in mainland Chinese Han population, allele A accounted for a higher proportion in good responders compared with poor responders at 33.3%, 24.6%, 25.2% in the Henan, Shanghai and total cohort, respectively, which means the G>A mutation might have certain impact on risperidone therapy. Recent research found that rs6706232 was significantly associated with UGT1A3 gene transcription and activity.…”
Section: Discussionmentioning
confidence: 54%
“… 18 , 19 For example, effect of rs6706232 on OTS167 (a novel synthetic anticancer agent molecule undergoing clinical development) glucuronidation formation rates was merely modest suggesting this SNP may not significantly contribute to OTS167 clearance. 20 In our study, rs6706232 was first found related with risperidone treatment in mainland Chinese Han population, allele A accounted for a higher proportion in good responders compared with poor responders at 33.3%, 24.6%, 25.2% in the Henan, Shanghai and total cohort, respectively, which means the G>A mutation might have certain impact on risperidone therapy. Recent research found that rs6706232 was significantly associated with UGT1A3 gene transcription and activity.…”
Section: Discussionmentioning
confidence: 54%
“…Second, there are some additional transformations with no training data evidence that we nevertheless kept in the validation set. For molecule 13 a “hypothesized glucuronide” is reported, an atypical N ‐glucuronide adduct to a pyridine ring. Molecules 18 and 23 show isoxazole ring cleavages.…”
Section: Resultsmentioning
confidence: 99%
“…However, some quinines inhibit UGTs, leading to adverse reactions. For example 44 , OTS167, an antineoplastic agent, is metabolized mainly by UGT1A1 and UGT1A3, and is inhibited by emodin (an inhibitor of UGT1A8 and UGT1A10). At the concentrations required to exert an antitumor effect, celastrol interacts with herbs and drugs 45 .…”
Section: Discussionmentioning
confidence: 99%